2022
DOI: 10.1038/s41467-022-34505-0
|View full text |Cite
|
Sign up to set email alerts
|

Nicking mechanism underlying the DNA phosphorothioate-sensing antiphage defense by SspE

Abstract: DNA phosphorothioate (PT) modification, with a nonbridging phosphate oxygen substituted by sulfur, represents a widespread epigenetic marker in prokaryotes and provides protection against genetic parasites. In the PT-based defense system Ssp, SspABCD confers a single-stranded PT modification of host DNA in the 5′-CPSCA-3′ motif and SspE impedes phage propagation. SspE relies on PT modification in host DNA to exert antiphage activity. Here, structural and biochemical analyses reveal that SspE is preferentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…SspE proteins, part of SspABCD-SspE phosphorothioationsensing bacterial defence systems, also contain predicted DUF262 and DUF1524 domains. Nevertheless, the reported role of SspE appears distinct from that observed for GrmSD and BrxU (Gao et al, 2022;Xiong et al, 2020). The SspE structure highlighted the DUF262 retains the conserved DGQQR motif in the nucleotidebinding pocket (Gao et al, 2022;Xiong et al, 2020).…”
Section: Duf262 and Duf1524mentioning
confidence: 86%
See 2 more Smart Citations
“…SspE proteins, part of SspABCD-SspE phosphorothioationsensing bacterial defence systems, also contain predicted DUF262 and DUF1524 domains. Nevertheless, the reported role of SspE appears distinct from that observed for GrmSD and BrxU (Gao et al, 2022;Xiong et al, 2020). The SspE structure highlighted the DUF262 retains the conserved DGQQR motif in the nucleotidebinding pocket (Gao et al, 2022;Xiong et al, 2020).…”
Section: Duf262 and Duf1524mentioning
confidence: 86%
“…Nevertheless, the reported role of SspE appears distinct from that observed for GrmSD and BrxU (Gao et al, 2022;Xiong et al, 2020). The SspE structure highlighted the DUF262 retains the conserved DGQQR motif in the nucleotidebinding pocket (Gao et al, 2022;Xiong et al, 2020). As per BrxU, SspE DUF262 can hydrolyse GTP, CTP, UTP and ATP indiscriminately.…”
Section: Duf262 and Duf1524mentioning
confidence: 90%
See 1 more Smart Citation
“…Notably, the DGQQR motif is thought to form part of a nucleotide binding pocket and to be required for nucleotide hydrolysis. Indeed, site-directed mutants of either TgvA or TgvB encoding substitutions in this motif previously shown to disrupt NTPase activity (4850), all resulted in a total loss of anti-phage activity (Fig. 4c-e).…”
Section: The Tgvab Defence System Is a Member Of The Gmrsd Family Of ...mentioning
confidence: 89%
“…Machnicka et al, showed that the predominant form of GmrSD is as a single multi-domain protein containing an N-terminal DUF262(GmrS) domain and a Cterminal DUF1524(GmrD) domain, separated by an alpha helical linker region (44). This domain organisation was subsequently confirmed by crystal structures of the related GmrSD family members BrxU, which also recognises and degrades DNA containing modified cytosines, and the phosphorothioate modification sensing enzyme SspE (48)(49)(50). Furthermore, biochemical experiments with these enzymes have shown that the N-terminal DUF262 likely functions as DNA modification sensor, and uses nucleotide binding and hydrolysis to regulate the activity of the C-terminal DUF1524, which functions as a nuclease to degrade non-self-DNA (48,50).…”
Section: The Tgvab Defence System Is a Member Of The Gmrsd Family Of ...mentioning
confidence: 93%